2009
DOI: 10.1177/1753465808103499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bosentan upon pulmonary hypertension in chronic obstructive pulmonary disease

Abstract: This preliminary report suggests that the use of Bosentan in the treatment of PH in COPD is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 16 publications
1
75
1
4
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Of the 24 publications that met the inclusion criteria for this systematic review (see Table 1), 16 compared tiotropium with placebo, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] seven compared tiotropium with an active comparator, [66][67][68][69][70][71][72] and one compared tiotropium with both placebo and an active comparator. 73 The QoL outcomes reported in the 24 included publications were mostly SGRQ and/or TDI (Tables 2 and 3).…”
Section: Summary Of Search Findingsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Of the 24 publications that met the inclusion criteria for this systematic review (see Table 1), 16 compared tiotropium with placebo, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] seven compared tiotropium with an active comparator, [66][67][68][69][70][71][72] and one compared tiotropium with both placebo and an active comparator. 73 The QoL outcomes reported in the 24 included publications were mostly SGRQ and/or TDI (Tables 2 and 3).…”
Section: Summary Of Search Findingsmentioning
confidence: 99%
“…Since these studies included patients with only mild to moderate pulmonary hypertension or exercise-induced pulmonary hypertension, it is important to note that the results may not apply to severe pulmonary hypertension in COPD. Some reports have shown improvement in functional status and hemodynamic parameters after bosentan therapy in COPD patients with severe pulmonary hypertension (12)(13)(14). Oxygenation and cardiac output were well maintained after bosentan therapy.…”
Section: Discussionmentioning
confidence: 92%
“…9 It was speculated that COPD patients with severe PH but only mild to moderate ventilatory impairment might benefit from vasoactive medication. 2 However, the reported effects of vasoactive drugs have been inconsistent [10][11][12][13] and reliable corroborating data are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7 The positive effect of the endothelin receptor antagonist bosentan on PH due to hypoxic PH and COPD was shown in animal models as well as in humans. [10][11][12] Stolz et al 13 concluded that bosentan failed to improve functional capacity in COPD patients without severe PH, but this cohort was not investigated by right heart catheterization, and the group treated with bosentan had a mean systolic pulmonary artery pressure of only 32 mm Hg.…”
Section: Pulmonary Hypertension In Copd E88mentioning
confidence: 99%